Mathematical Methods for Engineers and Geoscientists - Wälder, Olga. (Springer, 2017)
This fascinating work makes the link between the rarified world of maths and the down-to-earth one inhabited by engineers. It introduces and explains classical and modern mathematical procedures as applied to the real problems confronting engineers and geoscientists. Written in a manner that is understandable for students across the breadth of their studies, it lays out the foundations for mastering difficult and sometimes confusing mathematical methods. Arithmetic examples and figures fully support this approach, while all important mathematical techniques are detailed. Derived from the author's long experience teaching courses in applied mathematics, it is based on the lectures, exercises and lessons she has used in her classes.